2015
DOI: 10.1016/j.rmed.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of new-onset asthma diagnosed at adult age

Abstract: Further follow-up studies that recruit patients with new-onset adult asthma are needed to understand the prognostic factors in adult-onset asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…The use of two different kinds of spirometers, one with a turbine (MicroLoop) at baseline and one with ultra-sound transit time measurement (ndd EasyOne) at follow up may have affected the lung function data although calibration check was performed daily on both spirometers to minimise this bias. Furthermore, definitions of the age limit between early- and late-onset asthma vary widely in the literature [6,8,24]. However, the applied criteria for asthma and COPD are in line with recent research [18].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The use of two different kinds of spirometers, one with a turbine (MicroLoop) at baseline and one with ultra-sound transit time measurement (ndd EasyOne) at follow up may have affected the lung function data although calibration check was performed daily on both spirometers to minimise this bias. Furthermore, definitions of the age limit between early- and late-onset asthma vary widely in the literature [6,8,24]. However, the applied criteria for asthma and COPD are in line with recent research [18].…”
Section: Discussionmentioning
confidence: 89%
“…Analyses using pre-BD values showed larger decline per year, but did not influence on the role of the other determinants in the multivariate analyses. Previous studies have suggested accelerated lung function declines in asthma [28,29] and in a review of adult-onset asthma decline in FEV₁ varied between 25 and 95 ml per year [6]. Still, recent studies have found decline in FEV₁ in asthmatics of 25.3 [18] and 25.6 ml [30] per year, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the good prognosis strengthens the view. 36 A corresponding adult-onset group was recognized in the COREA study 6 and many studies have recognized childhood-onset atopic asthma. 5,7,10 A rather high annual lung function decline was seen after the reach of maximum point but this may be related to lung capacity because higher reversibility and higher maximal FEV 1 enable higher decline in lung function.…”
Section: Discussionmentioning
confidence: 98%